KEMANDIRIAN USAHA UMKM DI DAERAH PASIR PESISIR: PERAN NILAI JIWA WIRAUSAHA DAN PERILAKU KEWIRAUSAHAAN - Manurung, Haris (JOURNAL OF BUSINESS STUDIES, 2025)
The aim of this research is to find out how entrepreneurial behaviour and enthusiastic values influence entrepreneurial independence. The aim of this research is also to find out how entrepreneurial behaviour and enthusiastic values influence business independence. Primary data obtained from respondent questionnaires was used in this research. This research uses a purposive sampling technique, which involves establishing certain criteria for selecting samples. Twenty MSMEs that met certain requirements were obtained using this strategy. Multiple regression, t test, f test, determination test, classical assumption test, and descriptive test are some of the data analysis techniques used. Statistical package for social sciences (SPSS) version 25 was the data analysis tool used. The findings of this research indicate that cultivating an entrepreneurial mindset and acting in an entrepreneurial manner can significantly and profitably increase a company's level of independence.